PENGEMBANGAN APLIKASI WORKOUT BERBASIS ANDROID DENGAN FITUR PERSONALISASI PROGRAM LATIHAN DAN MONITORING KESEHATAN MENGGUNAKAN METODE HIGH INTENSITY INTERVAL TRAINING (HIIT) - Ilham Balit Luxfanza; Niki Ratama (Journal of Research and Publication Innovation, 2025)
This research aims to develop an Android-based workout application with personalized exercise program features and health monitoring using the high intensity interval training (HIIT) method. The research method used is the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collection, manufacturing, testing, distribution. Data was collected through interviews with Arum Gym owners and field observations to understand system requirements. The research results show that the developed workout application can facilitate gym members at Arum Gym with features such as personalized exercise programs and health monitoring. This workout application can also help gym members who experience difficulties during training at Arum Gym. Workout applications designed using the Multimedia Development Life Cycle (MDLC) method are effective in increasing efficiency in training. It is hoped that the implementation of this workout application can increase the motivation of gym members in training and help gym members who have difficulty when practicing workouts. The results of the analysis show that the majority of respondents gave positive responses, with an average score of 91% which shows a high level of satisfaction with the workout application being developed.